Some considerations on the growth performance of Mullus barbatus - Voliani A.; Abella A.; Auteri R. (Dynamique des populations marines, 1998)
The size structure of Mullus barbatus in the area between the Elba Island and the River Magra is studied. Survey data, gathered between 1985 to 1995, come from trawler using two different fishing gears. Multivariate analysis allowed classifying and pooling together hauls characterized by similar length composition. It was shown that size groups (corresponding to different cohorts) are concentrated in specific areas, whose shape is defined by hauls with similar size structure, changes during the year. The study highlighted the importance of the 0plus-age class in the population and in the catch. Given the massive presence of sexually mature individuals at the end of June (almost all the one year-old individuals spawn then), the cohorts were easily aged and this allowed the construction of a sort of age-length key. The age-length couples so obtained were compared with those derived from Von Bertalanffy growth curves estimated with a different approach but using the same source of data. It was concluded that none of the curves adequately describe the growth pattern for the whole life of the species. In fact, red mullet is characterized by an extremely fast growth during the first months of life, followed by a slower growth increment with time, hardly explainable with a single set of growth parameters.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)